METODE ITERATIF YANG DIPERCEPAT UNTUK Z-MATRIKS - Mildayani '; Syamsudhuha '; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses a preconditioned Gauss-Seidel method to solve a system of linear equation Ax = b, where A a strictly diagonally dominant Z-matrix. Preconditioning matrix to be used is P = (I + βU), where I is an identity matrix, U is a strictly upper triangular matrix and 0 < β ≤ 1. Numerical computations showthat the proposed preconditioned Gauss Seidel method is better than the standard Gauss Seidel method in solving a system of linear equation Ax = b.